Measuring restoration quality in urban forest greenways: insights for planning and management - Hong Wang; Yuxiang Liu; Ming-Juan Zhang; Xinxin Wang (Frontiers in Psychology)
IntroductionGreenways play a crucial role in enhancing citizens’ quality of life by providing restorative environments, particularly in settings such urban forests. While existing research underscores the superior restorative qualities of natural settings compared to urban environments, our understanding of how various urban forest greenways and seasonal variations shape restorative experiences remains limited.MethodsThis study investigates the restoration effects of various greenway scenes within the urban forests, including one urban greenway, one wilderness greenway and one tended greenway. A total of 55 university students viewed six videotaped greenway scenes in a randomized order. The urban and wilderness greenways were presented only for the summer scenes, while the tended greenway was shown across all four seasons. Physiological responses were measured using Electroencephalography (EEG), while psychological responses, including attentional levels and restorative experiences, were assessed with the Necker Cube and the Perceived Restorativeness Scale (PRS) respectively.ResultsThis study confirmed previous research that the natural environment restored attention, and watching a combination of different types of greenways and seasons increased attentional level. Findings suggest that tended greenways offer more effective restoration compared to urban greenways. Notably, tended greenways in spring, summer, and autumn were more restorative than winter scenes.DiscussionThese findings highlight how different types of greenways and seasonal variations can affect perceived restorativeness. They provide valuable insights for the planning and management of urban forest greenways, emphasizing the importance of considering route selection, planting design, and maintenance to enhance restorative benefits.